2001
DOI: 10.1046/j.1460-9592.2001.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Oozing from the Pericardium as an Etiology of Cardiac Tamponade Associated with Screw‐In Atrial Leads

Abstract: Screw-in atrial pacing leads are widely used. Cardiac tamponade is a complication. An 81-year-old woman with advanced atrioventricular block underwent permanent pacemaker implantation and subsequently developed cardiac tamponade. At surgery, the lead-tip screw was found penetrated through the right atrium but not through the pericardium. The source of bleeding was confirmed to scratching the inner pericardial membrane by the screw tip. Although cardiac tamponade due to perforation and leakage is known, tampona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…More than anything else, the chest CT showed an apparent perforation of the ventricle by the pacing lead. Although CT often fails to demonstrate minor displacement, 7) in this case it helped to confirm the tip of the perforating lead protruding into the pericardial cavity.…”
Section: Discussionmentioning
confidence: 75%
“…More than anything else, the chest CT showed an apparent perforation of the ventricle by the pacing lead. Although CT often fails to demonstrate minor displacement, 7) in this case it helped to confirm the tip of the perforating lead protruding into the pericardial cavity.…”
Section: Discussionmentioning
confidence: 75%
“…Permanent PM implantation may be complicated by cardiac perforation, which can lead to longer hospital stays, tamponade, or even death (Aizawa et al, 2001;Ellenbogen et al, 2002;Garcia-Bolao et al, 2001;Gershon et al 2000). The incidence of perforation after permanent PM reportedly is between 0.5% and 2%, but the predictors of perforation have not been defined (Hill, 1987;Sivakumaran et al, 2002).…”
Section: Lead-related Complicationsmentioning
confidence: 99%
“…Various complications of atrial lead fixation at the RAA or free wall have been reported [13][14][15][16][17][18][19][20][21] and in fact, considering the cardiac anatomy, it is surprising that perforation does not occur more frequently with atrial lead fixation at the RAA or free wall. Vlay et al reported that at the time of cardiac surgery, the tip of the helix of the right atrial electrode is occasionally visualized in patients with implanted pacemakers.…”
Section: Target Position Of the Atrial Leadmentioning
confidence: 99%
“…[1][2][3][4][5][6] It has also been reported that pacing at the right atrial septum (RAS) appears to be superior to that performed at the right atrial appendage (RAA) or free wall for preventing PAF with sinus bradycardia [7][8][9][10][11][12] and for reducing complications such as pericarditis, diaphragmatic stimulation, perforation, cardiac tamponade and pneumothorax. 7,[13][14][15][16][17][18][19][20][21] However, insertion of the lead at the RAS is sometimes technically difficult and time-consuming.…”
mentioning
confidence: 99%